Kinetic and thermodynamic properties of the folding and assembly of formate dehydrogenase - Ordu, Emel B.; Cameron, Gus; Clarke, Anthony R.; Karaguler, Nevin Gul (WILEY, 2009)
The folding mechanism and stability of dimeric formate dehydrogenase from Candida methylica was analysed by exposure to denaturing agents and to heat. Equilibrium denaturation data yielded a dissociation constant of about 10 (13) M for assembly of the protein from unfolded chains and the kinetics of refolding and unfolding revealed that the overall process comprises two steps. In the first step a marginally stable folded monomeric state is formed at a rate (k(1)) of about 2 x 10 (3) s (1) (by deduction k (1) is about10 (4)s (1)) and assembles into the active dimeric state with a bimolecular rate constant (k(2)) of about 2 x 10(4) M (1) s (1). The rate of dissociation of the dimeric state in physiological conditions is extremely slow (k (2) similar to 3 x 10 (7) s (1)). (C) 2009 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: Assembly mechanism; Folding mechanism; Formate dehydrogenase; Candida methylica; PROTEIN ASSOCIATION RATES; STABILITY; Biochemistry & Molecular Biology; Biophysics; Cell Biology